Intracellular rupture, exocytosis and actin interaction of endocytic vacuoles in pancreatic acinar cells: initiating events in acute pancreatitis. (6th June 2018) - Chvanov, Michael; De Faveri, Francesca; Moore, Danielle; Sherwood, Mark W.; Awais, Muhammad; Voronina, Svetlana; Sutton, Robert; Criddle, David N.; Haynes, Lee; Tepikin, Alexei V.
Abstract : Key points: Giant trypsin‐containing endocytic vacuoles are formed in pancreatic acinar cells stimulated with inducers of acute pancreatitis. F‐actin envelops endocytic vacuoles and regulates their properties. Endocytic vacuoles can rupture and release their content into the cytosol of acinar cells. Endocytic vacuoles can fuse with the plasma membrane of acinar cells and exocytose their content. Abstract: Intrapancreatic activation of trypsinogen is an early event in and hallmark of the development of acute pancreatitis. Endocytic vacuoles, which form by disconnection and transport of large post‐exocytic structures, are the only resolvable sites of the trypsin activity in live pancreatic acinar cells. In the present study, we characterized the dynamics of endocytic vacuole formation induced by physiological and pathophysiological stimuli and visualized a prominent actin coat that completely or partially surrounded endocytic vacuoles. An inducer of acute pancreatitis taurolithocholic acid 3‐sulphate and supramaximal concentrations of cholecystokinin triggered the formation of giant (more than 2.5 μm in diameter) endocytic vacuoles. We discovered and characterized the intracellular rupture of endocytic vacuoles and the fusion of endocytic vacuoles with basal and apical regions of the plasma membrane. Experiments with specific protease inhibitors suggest that the rupture of endocytic vacuoles is probably not induced by trypsin or cathepsin B. Perivacuolar filamentous actin (observed on the surface of ∼30% of endocytic vacuoles) may play a stabilizing role by preventing rupture of the vacuoles and fusion of the vacuoles with the plasma membrane. The rupture and fusion of endocytic vacuoles allow trypsin to escape the confinement of a membrane‐limited organelle, gain access to intracellular and extracellular targets, and initiate autodigestion of the pancreas, comprising a crucial pathophysiological event. Key points: Giant trypsin‐containing endocytic vacuoles are formed in pancreatic acinar cells stimulated with inducers of acute pancreatitis. F‐actin envelops endocytic vacuoles and regulates their properties. Endocytic vacuoles can rupture and release their content into the cytosol of acinar cells. Endocytic vacuoles can fuse with the plasma membrane of acinar cells and exocytose their content.